Improving Students’ Analytical Writing Skill by Writing Song Lyrics Analysis - Khoirunnisak; Yanti Sri Rezeki; Syarif Husin (Universitas Cokroaminoto Palopo, 2024)
This study aimed to improve students’ analytical writing skill by writing song lyrics analysis. This study was conducted as classroom action research in two cycles. The subject of this study is the eleventh grade Social 3 students of Man Kota Singkawang in the academic year 2023/2024 which consists of thirty one students. The data obtained were quantitative and qualitative data. Quantitative data was obtained through the result of writing task and the qualitative data was obtained through field notes. The result from data analysis showed that the use of song could make students enjoy the learning activity. In addition, the use of song lyrics could make students remember the vocabulary easier and writing song lyrics analysis could improve students’ analytical essay writing skill. It also can be seen from the improvement of students writing tasks’ scores in cycle 1 and cycle 2. The mean score in cycle 1 was 59,19 and it was improved to be 76,45 in cycle 2. In conclusion, using song lyrics had successfully improved analytical essay writing skill of students’ in the eleventh grade Social 3 at Man Kota Singkawang.